1997
DOI: 10.1073/pnas.94.7.2915
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soluble forms of nonchimeric type V adenylyl cyclases

Abstract: Type V adenylyl cyclase (ACV) belongs to the family of Ca 2+ - inhibited cyclases. We have generated two soluble forms of the enzyme containing the C1 or C1a region (which lacks the C-terminal 112 amino acids) linked to the C2 domain and compared their regulation with the full-length ACV. All three forms of ACV were stimulated by the α subunit of the stimulatory G protein G s (G sα ) and forskolin. However, the synergistic stimulation by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 39 publications
4
75
0
Order By: Relevance
“…The AC levels were identical in wild-type and Gnal + /À mice ( Figure 1i). Altogether these results show that the mutation of Gaolf did not alter the levels of AC5 and that the decreased basal and Mn 2 + -sensitive cyclase activity reflect the decrease in stimulatory G protein, as even the Mn 2 + -stimulated AC remains sensitive to the presence of G protein (Bender and Neer, 1983;Scholich et al, 1997).…”
Section: Dopamine-stimulated Ac Activity Is Decreased Inmentioning
confidence: 92%
“…The AC levels were identical in wild-type and Gnal + /À mice ( Figure 1i). Altogether these results show that the mutation of Gaolf did not alter the levels of AC5 and that the decreased basal and Mn 2 + -sensitive cyclase activity reflect the decrease in stimulatory G protein, as even the Mn 2 + -stimulated AC remains sensitive to the presence of G protein (Bender and Neer, 1983;Scholich et al, 1997).…”
Section: Dopamine-stimulated Ac Activity Is Decreased Inmentioning
confidence: 92%
“…32). The proteins were expressed in the Escherichia coli strain TP2000, which is incapable of producing cAMP (42).…”
Section: Methodsmentioning
confidence: 99%
“…(31), although higher concentrations were not explored. Recently, a chimeric, soluble form of AC5, comprising its fused cytosolic (C1 and C2) domains was reported to display high affinity inhibition by Ca 2ϩ , which was lost upon truncation of the C1 region (32). Furthermore, AC2, which is classified as a Ca 2ϩ -insensitive adenylyl cyclase, displays inhibition in response to high concentrations of Ca 2ϩ .…”
Section: ؉mentioning
confidence: 99%
“…2 and 3). The N-terminal domain of ACV did not exert a significant effect on the enzymatic properties or on certain regulatory modes (such as the inhibition mediated by G␣ i or calcium (12,35)). Replacement of the N terminus of ACVI with that of ACV did not affect the enzymatic properties of ACVI either (Table I) but markedly altered the inhibition mediated by D2s-R (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the C1b domain has been implicated in the regulation of AC isozymes mediated by Ca 2ϩ /calmodulin, calcineurin, or protein kinase A (8 -11). In addition, the C1b domain of ACV and ACVII has been shown to modulate G␣ s -evoked activation by interacting with catalytic core complexes (12,13). Others and we have shown that another variable region, the N-terminal domain, also significantly contributes to the regulation of AC activity (14,15).…”
mentioning
confidence: 95%